Characteristics and mechanism of malachite green decolorization by Enterobacter sp. CV-b - LI Gang; DU Linna; XU Fangcheng; WANG Yang; PAN Xiu (浙江大学学报. 农业与生命科学版)
Malachite green (MG) is a typical triphenylmethane dye that has been extensively used in ceramics, dyeing, textile and leather industries, etc. Meanwhile, MG can also be used as insect repellant, insecticide and anti- microbial agents in aquaculture industry. However, it has been reported that MG is difficult to degrade and has potential carcinogenicity and genotoxicity for humans, animals, and microorganisms. As a result, MG has been prohibited from being used in aquaculture by Food and Drug Administration of the United States, United Kingdom, China, European Union, and some other countries. Therefore, to remove MG residue in the aquatic environment, protect human beings and maintain the ecological balance, screening of microorganisms for biodegradation of MG is very necessary and important. Biodegradation of MG by microorganisms has gained more and more attention due to its inexpensive and eco-friendly feature. Raoultella sp., Pandoraea sp., Pseudomonas sp. and Arthrobacter sp. have been reported to have potential ability for biodegradation of MG. The degradation behavior was distinctly affected by culture condition and environmental factors.In this study, a bacterial strain named as Enterobacter sp. CV-b was isolated, and the characteristics of MG decolorization by Enterobacter sp. CV-b were investigated using single-factor experiments, then the enzymes and metabolites related to MG degradation were detected by ultraviolet-visible spectrophotometry, Fourier transform infrared spectroscopy, and gas chromatography-mass spectrometry technologies, to screen for in situ bacteria with stronger environmental adaptability.The results indicated that most of the tested carbon sources had no significant effect on decolorization, and starch was the optimal carbon source for promotion of decolorization. In the initial incubation period, the inorganic nitrogen source NH4Cl slightly inhibited the decolorization of MG, and the inhibition effect became weaker with time. Meanwhile, the inorganic nitrogen source NaNO3 could slightly enhance the decolorization of MG. However, most of the organic nitrogen sources significantly enhanced decolorization, and peptone was the optimal nitrogen source for MG decolorization. Under the condition of pH 5.0-10.0 and 20-50 ℃, MG decolorization percentage by the strain CV-b was over 92% after 6 h incubation, indicating this strain has strong environmental adaptability with broad pH and temperature range. After 6 h incubation, MG decolorization percentage by the strain reached 90% with the initial MG concentration below 900 mg/L, suggesting its great potential in highly efficient biodegradation of MG. Besides, Cu2+ was observed to inhibit MG decolorization significantly. Enzyme activity data showed that tyrosinase might be involved in the MG degradation by the strain CV-b. Meanwhile, the results of metabolite analysis indicated that (dimethylamino-phenyl)-phenyl-methanone was one of the major products of MG degradation by the strain CV-b.In conclusion, this strain has a great potential in the application of MG bioremediation due to its strong environmental adaptability with broad pH and temperature range, and high degradation percentage of MG with high initial dye concentration. Moreover, the related enzyme analysis and metabolite detection will be helpful to understand the mechanism of MG decolorization by the strain CV-b.